2017
DOI: 10.1186/s13071-017-2024-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparative speed of kill of sarolaner (Simparica®) and afoxolaner (NexGard®) against induced infestations of Ixodes holocyclus on dogs

Abstract: BackgroundThe Australian paralysis tick, Ixodes holocyclus, causes paralysis predominantly in dogs and cats in the Eastern coastal regions of Australia. Rapid onset of effect of a parasiticide is critical to minimize the deleterious effects of these tick infestations, especially tick paralysis caused by the salivary neurotoxin. The speed of kill of a novel orally administered isoxazoline parasiticide, sarolaner chewable tablets (Simparica®), against I. holocyclus on dogs was evaluated and compared with afoxola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 34 publications
(36 reference statements)
2
8
0
1
Order By: Relevance
“…The findings of lotilaner efficacy against I. holocyclus in this study parallel those of a report of the efficacy of sarolaner and afoxolaner in eliminating existing burdens and post-treatment infestations through 35 days after treatment [ 19 ]. Extending well beyond the findings of that study, we have demonstrated the potency of lotilaner in providing a high level of efficacy through at least 12 weeks after treatment against I. holocyclus when evaluated at 72 h post-treatment or re-infestation.…”
Section: Resultssupporting
confidence: 88%
“…The findings of lotilaner efficacy against I. holocyclus in this study parallel those of a report of the efficacy of sarolaner and afoxolaner in eliminating existing burdens and post-treatment infestations through 35 days after treatment [ 19 ]. Extending well beyond the findings of that study, we have demonstrated the potency of lotilaner in providing a high level of efficacy through at least 12 weeks after treatment against I. holocyclus when evaluated at 72 h post-treatment or re-infestation.…”
Section: Resultssupporting
confidence: 88%
“…Both free and attached ticks were characterized as either live or dead as described previously [ 58 ]. Moribund ticks were characterized and included in the live counts as previously described [ 49 ]. All the tick counts and assessments were performed by laboratory technicians who were experienced and trained on validated laboratory methods of tick counting and assessments.…”
Section: Methodsmentioning
confidence: 99%
“…Sarolaner (Simparica™, Zoetis) chewable tablet dosed at 2 mg/kg body weight, a potent ecto-parasiticide, has excellent efficacy against ticks, fleas and mites [ 6 ] and has been demonstrated to provide rapid and sustained efficacy against I. holocyclus [ 49 ]. To broaden the spectrum of activity, a new novel oral chewable combination product delivering 1.2 mg/kg sarolaner, 24 µg/kg moxidectin and 5 mg/kg pyrantel (Simparica Trio™, Zoetis) has been approved in USA, Canada, Europe and Australia.…”
Section: Introductionmentioning
confidence: 99%
“…In a laboratory study with dogs, an oral dose of sarolaner provided 86.2 and 96.5% reductions in Ixodes holocyclus at 8 and 12 h, respectively whereas an oral dose of afoxolaner provided 21.3 and 85.0% reductions at 8 and 12 h, respectively. When treated dogs were challenged at day 35, sarolaner and afoxolaner provided 65.2 and 21.0% efficacy at 12 h, respectively [ 77 ]. Oral doses of sarolaner, moxidectin, and pyrantel to laboratory dogs provided 99.7% reductions in C. f. felis for at least 35 days with no eggs being laid during the 35 days.…”
Section: Chemical Treatmentsmentioning
confidence: 99%